Cantwell, Theresa Squires. Black and white photograph of two girls in a field from Theresa Squires Cantwell's personal photograph collection. - Barrett, Terra (1945)
Left to right: Theresa Cantwell (Squires), and Eileen Ottawa (Squires) in parents yard.